Implementation of a High-Risk Outpatient Clinic for Children with Complex Congenital Heart Disease in a Reference Service in Brazil - Gustavo Foronda; Vanessa Ferreira Amorim de Melo; Claudia Regina Pinheiro de Castro Grau; Ingrid Magatti Piva; Gláucia Maria Penha Tavares; Ana Cristina Sayuri Tanaka; Nana Miura (2023)
Background: Children with congenital heart disease (CHD), even after surgical approaches, and especially those who undergo staged procedures in the first months of life, remain vulnerable to readmissions and complications, requiring very close monitoring and differentiated intervention strategies. Methods: Descriptive and exploratory study, of the experience report type, which presents the process of building the high-risk outpatient clinic for complex congenital heart diseases (AAR) at the Instituto do Coração (InCor). Results: Report of the path taken to structure the AAR, demonstrating the organization, interface with the multidisciplinary team, admission and discharge criteria, training, and patient profile. In these five years of care, 275 patients were treated, 59.65% with biventricular interstage physiology, followed by univentricular interstage physiology (34.55%), residual defects after surgical procedures (3.63%), tumors with risk of mechanical obstruction (1.45%) and patients with an intrauterine approach (0.72%). The significant number of critical patients who were successfully discharged from hospital (44.72%), the low mortality rate due to sudden deaths at home and the high adherence to follow-up corroborate the impact of this specialized assistance. Conclusions: Despite the limitations of the study, this experience report showed that with few resources, there is the possibility of organizing an AAR with differentiated care, with the objective of early detection and treatment of residual injuries, identification of early interventions, education of parents for follow-up of their children, resulting in individualized treatment, promoting a better quality of life for this population.